Hydrogel electrolyte, aqueous zinc-based battery and preparation method of aqueous zinc-based battery
By preparing hydrogel electrolytes and combining them with specific positive and negative electrode materials, the problem of performance degradation of aqueous zinc-based batteries at low temperatures was solved, and aqueous zinc-based batteries with high cycle stability and high voltage were achieved, which are suitable for low-temperature environments.
Patent Information
- Application Number
- CN202510967028.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-10-10
AI Technical Summary
Aqueous zinc-based batteries suffer from severe performance degradation and poor cycle stability at extremely low temperatures, which limits their application in low-temperature environments.
A hydrogel electrolyte is used, and a mixture of solvents, electrolytes, hydrophilic monomers, cross-linkers and photoinitiators is used to prepare the hydrogel electrolyte by ultraviolet light reaction. Combined with manganese-based, nickel-based and Prussian blue analogue positive electrodes, zinc foil, zinc powder or zinc oxide negative electrodes, a low-temperature resistant and highly cycle-stable aqueous zinc-based battery is formed.
At low temperatures, the battery voltage can reach above 1.8V, and the cycle performance exceeds 3,000 cycles, showing a high discharge platform and high coulombic efficiency, making it suitable for driving low-temperature devices.
Smart Images

Figure CN120767443A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of energy storage technology, and in particular relates to a hydrogel electrolyte, an aqueous zinc-based battery, and a preparation method thereof. Background Art
[0002] Organic lithium-ion battery systems (LIBs) hold the largest market share in the energy storage field. However, the organic electrolytes used in LIBs are toxic and flammable, posing significant safety risks. Furthermore, the scarcity of lithium metal resources leads to high LIB costs. Therefore, aqueous zinc-based batteries, with their high safety, low cost, and readily available zinc metal, have become a complementary technology in the current energy storage market, playing an irreplaceable role in applications such as electric bicycles and oilfield exploration.
[0003] However, the intrinsic properties of aqueous zinc-based batteries, such as low voltage, poor cycle stability, and difficulty in stable operation under extreme external conditions, limit their further development. For example, vanadium-based zinc-based batteries have low voltage and poor cycle stability. The positive electrode crystal structure of pure embedded manganese dioxide zinc-based batteries is easily deactivated and has poor low-temperature performance. Existing aqueous zinc-based batteries can usually only exert their best electrochemical performance between 15-30 degrees Celsius. Once the ambient temperature is below 15 degrees Celsius, the battery performance decreases significantly. When the temperature is below 0 degrees Celsius, the battery performance decays sharply.
[0004] Therefore, it is necessary to develop an aqueous zinc-based battery with low temperature resistance and high cycle stability to lay the foundation for the large-scale use of aqueous zinc-based batteries. Summary of the Invention
[0005] To address the above problems, the present application discloses a hydrogel electrolyte, the synthesis raw materials of which are a solvent, an electrolyte, a hydrophilic monomer, a crosslinker and a photoinitiator in a molar ratio of 0.5-1.5:0.01-0.1:0.05-0.5:0.001-0.01:0.0001-0.001.
[0006] Furthermore, the solvent is water or a mixed solution of water and polyhydroxy lower alcohol.
[0007] Furthermore, the electrolyte is one or more of zinc sulfate, zinc acetate, manganese sulfate, manganese acetate, sulfuric acid, lithium hydroxide and potassium hydroxide.
[0008] Furthermore, the hydrophilic monomer is acrylamide and / or methacrylic acid sulfobetaine.
[0009] Furthermore, the cross-linking agent is lithium magnesium silicate and / or glucose monohydrate.
[0010] The present application also discloses an aqueous zinc-based battery, comprising the above-mentioned hydrogel electrolyte.
[0011] Furthermore, the aqueous zinc-based battery has a positive electrode formed of one or more of a manganese-based, a nickel-based, and a Prussian blue analog.
[0012] Furthermore, the aqueous zinc-based battery has a negative electrode formed of one or more of zinc foil, zinc powder and zinc oxide.
[0013] The present application also discloses a method for preparing a hydrogel electrolyte, comprising: mixing the solvent with the electrolyte to obtain an electrolyte solution; A hydrophilic monomer, a cross-linking agent and a photoinitiator are added to the electrolyte solution and then placed under ultraviolet light for reaction to obtain a hydrogel electrolyte.
[0014] The present application also discloses a method for preparing the aqueous zinc-based battery, comprising: synthesizing a hydrogel containing a hydrophilic functional group and an electrolyte as a hydrogel electrolyte; The hydrogel electrolyte, positive electrode and negative electrode are assembled into a battery.
[0015] The technical effects and advantages of this application are: This application solves the shortcomings of poor cycle stability and low-temperature resistance of aqueous zinc-based batteries through hydrogel electrolyte technology. It is suitable for positive electrodes of manganese-based, nickel-based, and Prussian blue analogue materials. The resulting aqueous zinc-based battery has a cycle performance of more than 3,000 cycles, and the voltage can reach above 1.8V at low temperatures.
[0016] Other features and advantages of the present application will be described in the following description, and in part will become apparent from the description, or will be understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained by the structures indicated in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0018] Figure 1 Schematic diagram of the cross-linking process of the hydrogel electrolyte according to an embodiment of the present application. DETAILED DESCRIPTION
[0019] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0020] Currently, aqueous zinc-based batteries face numerous challenges. Generally, improvements in the electrochemical performance of zinc-based batteries are achieved through electrolyte modification. Common aqueous zinc-based electrolytes include highly concentrated salt electrolytes, organic / aqueous mixed electrolytes, hydrogel electrolytes, and additive solution electrolytes. Each electrolyte has its own advantages and disadvantages. Compared to other aqueous electrolytes, hydrogel electrolytes generally exhibit superior overall performance.
[0021] Based on this, the present application provides a hydrogel electrolyte, the synthetic raw materials of which are a solvent, an electrolyte, a hydrophilic monomer, a crosslinker and a photoinitiator in a molar ratio of 0.5-1.5:0.01-0.1:0.05-0.5:0.001-0.01:0.0001-0.001.
[0022] In some embodiments of the present application, the solvent is water or a mixed solution of water and polyhydroxy lower alcohols, and the molar ratio of water to polyhydroxy lower alcohols in the mixed solution is 2-5:1, preferably 2:1, wherein polyhydroxy lower alcohols refer to a class of organic compounds containing multiple hydroxyl groups and a small number of carbon atoms (usually ≤6) in the molecule. They have high polarity, strong water solubility and good biocompatibility. Common polyhydroxy lower alcohols include diols (such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol), triols (such as glycerol, 1,2,3-hexanetriol) and polyols (such as erythritol, xylitol, sorbitol).
[0023] In some embodiments of the present application, the electrolyte is one or more of zinc sulfate, zinc acetate, manganese sulfate, manganese acetate, sulfuric acid, lithium hydroxide, and potassium hydroxide.
[0024] In some embodiments of the present application, the hydrophilic monomer is acrylamide and / or methacrylic acid sulfobetaine.
[0025] In some embodiments of the present application, the cross-linking agent is lithium magnesium silicate and / or glucose monohydrate.
[0026] The present application also discloses an aqueous zinc-based battery, comprising the above-mentioned hydrogel electrolyte.
[0027] In some embodiments of the present application, the aqueous zinc-based battery has a positive electrode formed by one or more of a manganese-based, a nickel-based, and a Prussian blue analogue, wherein the manganese-based includes manganese dioxide, lithium manganate, etc., the nickel-based includes nickel hydroxide, etc., and the Prussian blue analogue (PBA) is an open framework material that is widely used as an electrode material in various battery systems due to its adjustable ion channel, low cost, and high stability, including a ferrous Prussian blue analogue (Fe4[Fe(CN)6]3), a manganese Prussian blue analogue (KFeMn[Fe(CN)4]), etc.
[0028] In some embodiments of the present application, the aqueous zinc-based battery has a negative electrode formed by one or more of a zinc foil, a zinc powder, and zinc oxide.
[0029] The present application also discloses a preparation method of the above-mentioned hydrogel electrolyte, comprising: The solvent is mixed with the electrolyte to obtain an electrolyte solution; the hydrophilic monomer, the crosslinking agent, and the photoinitiator are added to the electrolyte solution, and then the electrolyte solution is subjected to reaction under ultraviolet light to obtain the hydrogel electrolyte. The hydrophilic monomer is acrylamide and / or methacrylic acid sulfobetaine, the crosslinking agent is magnesium lithium silicate and / or glucose monohydrate, and the molar ratio of water, the electrolyte, the hydrophilic monomer, the crosslinking agent, the photoinitiator, and the photoinitiator is 0.5-1.5:0.01-0.1:0.05-0.5:0.001-0.01:0.0001-0.001. The process of synthesizing the hydrogel electrolyte is as shown in Figure 1 The present application adopts a physical crosslinking mode, the crosslinking agent realizes crosslinking based on various hydrogen bonds of hydrophilic functional groups and electrostatic forces, the hydrophilic monomer can be modified by mixing acrylamide and methacrylic acid sulfobetaine, so that the low-temperature resistance and the high cycle stability of the aqueous zinc-based battery are greatly improved.
[0030] The present application also discloses a preparation method of the above-mentioned aqueous zinc-based battery, comprising: The hydrogel containing the hydrophilic functional group and the electrolyte is synthesized as the hydrogel electrolyte; The hydrogel electrolyte, the positive electrode, and the negative electrode are assembled into the battery.
[0031] In order to better explain the present application, the following embodiments are provided.
[0032] Embodiment 1 S1: 1 mol of water and electrolyte (0.02 mol of zinc sulfate + 0.01 mol of manganese sulfate) are mixed to obtain an electrolyte solution; S2: Add a hydrophilic monomer (0.07 mol acrylamide + 0.003 mol methyl acrylate sulfobetaine), a crosslinker (0.005 mol glucose monohydrate and 0.003 mol lithium magnesium silicate) and 0.0005 mol photoinitiator 2959 to the electrolyte and then react under ultraviolet light for 40 minutes to obtain a hydrogel electrolyte.
[0033] S3: Assemble the hydrogel electrolyte, manganese dioxide positive electrode and zinc foil negative electrode into a battery.
[0034] The mechanical properties of the synthesized hydrogel electrolyte were tested, and the results showed that the elongation at break of the hydrogel electrolyte was 1800% and the fracture strength was 0.2MPa; the electrochemical stability window of the synthesized hydrogel electrolyte was tested, and the results showed that the electrochemical stability window of the hydrogel electrolyte was 3.2V; the corrosion potential of the hydrogel on the zinc negative electrode was tested, and the results showed that the corrosion potential of the zinc negative electrode was -1.04V.
[0035] The assembled aqueous zinc-based battery was tested for cyclic voltammetry and rate performance. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.9 V) and high rate performance (10 A g -1 The current density is 400 mAh g -1 capacity).
[0036] The charge-discharge curves and cycle performance of the assembled aqueous zinc-based battery were tested. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.9V), high coulombic efficiency (about 100%), and high capacity (600 mAh g) under long life (3000 cycles). -1 ).
[0037] The assembled aqueous zinc-based battery can drive a fluorescent watch at room temperature.
[0038] Example 2 S1: 0.5 mol of water and electrolyte (0.005 mol of zinc acetate + 0.005 mol of manganese acetate) were mixed to obtain an electrolyte solution; S2: Add a hydrophilic monomer (0.045 mol acrylamide + 0.005 mol methyl acrylate sulfonate betaine), a crosslinker (0.005 mol glucose monohydrate and 0.005 mol lithium magnesium silicate) and 0.0001 mol photoinitiator 2959 to the electrolyte and then react under ultraviolet light for 40 minutes to obtain a hydrogel electrolyte.
[0039] S3: Assemble the battery with a hydrogel electrolyte, a manganese-based Prussian blue analogue positive electrode (KFeMn[Fe(CN)4]) and a zinc powder negative electrode.
[0040] The mechanical properties of the synthesized hydrogel electrolyte were tested, and the results showed that the elongation at break of the hydrogel electrolyte was 1200% and the fracture strength was 0.1 MPa; the electrochemical stability window of the synthesized hydrogel electrolyte was tested, and the results showed that the electrochemical stability window of the hydrogel electrolyte was 3.0V; the corrosion potential of the hydrogel electrolyte on the zinc negative electrode was tested, and the results showed that the corrosion potential of the zinc negative electrode was -1.08V.
[0041] The assembled aqueous zinc-based battery was tested for cyclic voltammetry and rate performance. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.7V) and high rate performance (2A g -1 The current density is 100 mAh g -1 capacity).
[0042] The charge-discharge curves and cycle performance of the assembled aqueous zinc-based battery were tested. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.7V), high coulombic efficiency (99%), and high capacity (90 mAh g) under long life (10,000 cycles). -1 ).
[0043] The assembled aqueous zinc-based battery can drive the fluorescent panel at room temperature.
[0044] Example 3 S1: 1.5 mol of water and electrolyte (0.5 mol of potassium hydroxide + 0.5 mol of lithium hydroxide) are mixed to obtain an electrolyte solution; S2: Add a hydrophilic monomer (0.4 mol acrylamide + 0.1 mol methyl acrylate sulfonate betaine), a crosslinker (0.005 mol glucose monohydrate and 0.005 mol lithium magnesium silicate) and 0.001 mol photoinitiator 2959 to the electrolyte and then react under ultraviolet light for 40 minutes to obtain a hydrogel electrolyte.
[0045] S3: Assemble the hydrogel electrolyte, nickel hydroxide positive electrode and zinc oxide negative electrode into a battery.
[0046] The mechanical properties of the synthesized hydrogel electrolyte were tested, and the results showed that the elongation at break of the hydrogel electrolyte was 2400% and the fracture strength was 1.0 MPa; the electrochemical stability window of the synthesized hydrogel electrolyte was tested, and the results showed that the electrochemical stability window of the hydrogel electrolyte was 3.4 V; the corrosion potential of the hydrogel on the zinc negative electrode was tested, and the results showed that the corrosion potential of the zinc negative electrode was -1.1 V.
[0047] The assembled aqueous zinc-based battery was tested for cyclic voltammetry and rate performance. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.75V) and high rate performance (5A g -1 The current density shows 150 mAh g-1 capacity).
[0048] The charge-discharge curves and cycle performance of the assembled aqueous zinc-based battery were tested. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.75V), high coulombic efficiency (98%), and high capacity (140 mAh g) under long life (500 cycles) at -20 degrees Celsius. -1 ).
[0049] The assembled aqueous zinc-based battery can drive an electric toy car at minus 20 degrees Celsius.
[0050] Example 4 S1: 1.1 mol of water and electrolyte (0.08 mol of zinc sulfate + 0.01 mol of manganese sulfate + 0.01 mol of sulfuric acid) were mixed to obtain an electrolyte solution; S2: Add a hydrophilic monomer (0.3 mol acrylamide + 0.1 mol methyl acrylate sulfobetaine), a crosslinker (0.006 mol glucose monohydrate and 0.002 mol lithium magnesium silicate) and 0.0007 mol photoinitiator 2959 to the electrolyte and then react under ultraviolet light for 40 minutes to obtain a hydrogel electrolyte.
[0051] S3: Assemble the hydrogel electrolyte, lithium manganese oxide positive electrode and zinc foil negative electrode into a battery.
[0052] The mechanical properties of the synthesized hydrogel electrolyte were tested, and the results showed that the elongation at break of the hydrogel electrolyte was 1400% and the fracture strength was 0.4MPa; the electrochemical stability window of the synthesized hydrogel electrolyte was tested, and the results showed that the electrochemical stability window of the hydrogel electrolyte was 3.1V; the corrosion potential of the hydrogel on the zinc negative electrode was tested, and the results showed that the corrosion potential of the zinc negative electrode was -1.02V.
[0053] The assembled aqueous zinc-based battery was tested for cyclic voltammetry and rate performance. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.99V) and high rate performance (1 mA cm-2) at -20 degrees Celsius. -2 The current density shows 600 mAhg -1 capacity).
[0054] The charge-discharge curves and cycle performance of the assembled aqueous zinc-based battery were tested. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.99V), high coulombic efficiency (about 95%), and high capacity (600 mAh g) under long life (1000 cycles) at -20 degrees Celsius. -1 ).
[0055] The assembled aqueous zinc-based battery can drive a small electric fan at minus 20 degrees Celsius.
[0056] Example 5 S1: 1.2 mol of a water / ethylene glycol mixed solution (molar ratio of water to ethylene glycol is 2:1) and an electrolyte (0.08 mol of zinc sulfate + 0.01 mol of manganese acetate) are mixed to obtain an electrolyte solution; S2: Add a hydrophilic monomer (0.2 mol acrylamide + 0.2 mol methacrylic acid sulfobetaine), a crosslinker (0.005 mol glucose monohydrate and 0.003 mol lithium magnesium silicate) and 0.0008 mol photoinitiator 2959 to the electrolyte and react under ultraviolet light for 40 minutes to obtain a hydrogel electrolyte; S3: Assemble the battery by hydrogel electrolyte, iron-based Prussian blue analog (Fe4[Fe(CN)6]3) positive electrode and zinc foil negative electrode.
[0057] The mechanical properties of the synthesized hydrogel electrolyte were tested, and the results showed that the elongation at break of the hydrogel electrolyte was 1100% and the fracture strength was 0.8 MPa; the electrochemical stability window of the synthesized hydrogel electrolyte was tested, and the results showed that the electrochemical stability window of the hydrogel electrolyte was 3.6V; the corrosion potential of the hydrogel on the zinc negative electrode was tested, and the results showed that the corrosion potential of the zinc negative electrode was -1.2V.
[0058] The assembled aqueous zinc-based battery was tested for cyclic voltammetry and rate performance. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.9V) and high rate performance (1 mA cm-2) at -20 degrees Celsius. -2 The current density shows 160 mAhg -1 capacity).
[0059] The assembled aqueous zinc-based battery charge and discharge curves and cycle performance were tested. The results showed that the aqueous zinc-based battery exhibited a high discharge platform (1.9V), high coulombic efficiency (about 99%) and high capacity (120 mAh g) under long life (5000 cycles) at -20 degrees Celsius. -1 ).
[0060] The assembled aqueous zinc-based battery can drive an electronic watch at minus 20 degrees Celsius.
[0061] In summary, this application solves the shortcomings of poor cycle stability and low-temperature resistance of aqueous zinc-based batteries by designing hydrogel electrolytes. It is suitable for manganese-based, nickel-based and Prussian blue analogue positive electrodes. The prepared aqueous zinc-based battery has a cycle performance of more than 3000 cycles, and the voltage can reach above 1.8 V at low temperatures.
[0062] Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A hydrogel electrolyte, characterized in that The synthetic raw materials of the hydrogel electrolyte are a solvent, an electrolyte, a hydrophilic monomer, a crosslinking agent and a photoinitiator in a molar ratio of 0.5-1.5:0.01-0.1:0.05-0.5:0.001-0.01:0.0001-0.
001.
2. The hydrogel electrolyte according to claim 1, characterized in that The solvent is water or a mixed solution of water and polyhydroxy lower alcohol.
3. The hydrogel electrolyte according to claim 1, characterized in that The electrolyte is one or more of zinc sulfate, zinc acetate, manganese sulfate, manganese acetate, sulfuric acid, lithium hydroxide and potassium hydroxide.
4. The hydrogel electrolyte according to claim 1, wherein The hydrophilic monomer is acrylamide and / or methacrylic acid sulfobetaine.
5. The hydrogel electrolyte according to claim 1, characterized in that The cross-linking agent is lithium magnesium silicate and / or glucose monohydrate.
6. An aqueous zinc-based battery, characterized in that: The invention comprises the hydrogel electrolyte according to any one of claims 1 to 5.
7. An aqueous zinc-based battery according to claim 6, characterized in that: The aqueous zinc-based battery has a positive electrode formed of one or more of a manganese-based, a nickel-based, and a Prussian blue analog.
8. The aqueous zinc-based battery according to claim 6, characterized in that: The aqueous zinc-based battery has a negative electrode formed of one or more of zinc foil, zinc powder and zinc oxide.
9. A method for preparing the hydrogel electrolyte according to any one of claims 1 to 5, characterized in that: include: mixing the solvent and the electrolyte to obtain an electrolyte solution; A hydrophilic monomer, a cross-linking agent and a photoinitiator are added to the electrolyte solution and then placed under ultraviolet light for reaction to obtain a hydrogel electrolyte.
10. A method for preparing an aqueous zinc-based battery according to any one of claims 6 to 8, characterized in that: include: synthesizing a hydrogel containing a hydrophilic functional group and an electrolyte as a hydrogel electrolyte; The hydrogel electrolyte, the positive electrode and the negative electrode are assembled into a battery.
Citation Information
Patent Citations
High-strength physical crosslinking hydrogel and elastomer composition and preparation method thereof
CN106279722A
Thermosensitive high strength and toughness nano-composite hydrogel and preparation method thereof
CN108794768A
Polyanion zinc salt hydrogel electrolyte and zinc battery system
CN114195935A
Hydrogel electrolyte for zinc-manganese battery, preparation method of hydrogel electrolyte, zinc-manganese battery and preparation method of zinc-manganese battery
CN114853942A
Gel electrolyte with wide temperature range, preparation method of gel electrolyte, aqueous zinc ion battery and application of aqueous zinc ion battery
CN118173916A